Microscopic mechanisms of deformation transfer in high dynamic range branched nanoparticle deformation sensors - Shilpa N. Raja (Nature Portfolio, 2018)
Tetrapod quantum dots are promising nanoscale stress sensors because of their non-invasive sensing technique, but sensor versatility has not yet been assessed. Here the authors show that tetrapod quantum dots exhibit a large dynamic range and excellent sensing versatility in a multitude of polymers.